Metal-free synthesis of quinazolinones without any additives in water. Issue 50 (4th May 2016) - Hu, Ben-Quan; Cui, Jie; Wang, Li-Xia; Tang, Ya-Lin; Yang, Luo
Abstract : Here we report that an excess amount of aldehyde, in particular, aliphatic aldehyde, without any additives, efficiently facilitates the oxidation of aminal intermediates to quinazolinones in pure water. Abstract : Here we report that an excess amount of aldehyde, in particular, aliphatic aldehyde, without any additives, efficiently facilitates the oxidation of aminal intermediates to quinazolinones in pure water.